Age structure of the birch stands in the Left-Bank Forest-Steppe of Ukraine - Meshkova, V. L.; Koshelyaeva, Ya. V. (Forestry and Forest Melioration, 2019)
Introduction Silver birch (Betula pendula Roth) in the forest fund of the State Forest Resources Agency of Ukraine covers only 5.7% of the forest-covered area. Considering a high ecological meaning of this species, its proportion should be increased. Recently its health condition has worsened in many regions. Our previous studies showed that among the trees with the diameter over 20 cm, a diameter of dead trees exceeded that of living ones. This indirectly indicates that the standard age of maturity and, accordingly, the age of the main felling in birch stands is overstated. Due to a small proportion of the birch in stands and its relatively early mortality, valuable properties of this species are far from being fully utilized. We assumed that when evaluating the maturity age for forest species, it is necessary to take into account not their productivity dynamics only, but also the risk of their health condition worsening with age, which, in turn, brings about deterioration in the quality of timber products. The aim of the research was to define the features of the age structure of silver birch stands in the Left-Bank Forest-Steppe considering forest site conditions, origin, site index and proportion of this species in the forest composition. Materials and Methods We analyzed the Ukrderzhlisproekt Production Association Database (by 01.01.2011) for the State Forest Enterprises located in the Left-Bank Forest-Steppe. We studied the data for subcompartments with silver birch as the main forest-forming species according to 10-year age classes for different forest site conditions, origin (natural and artificial seed origin, vegetative origin), site index, and proportion of silver birch in the stand composition. According to the method of Yu. P. Demakov, the area proportion of each 10-year age class was evaluated for each sample of subcompartments with respective forest site condition, origin, site index, and proportion of silver birch in the stand composition. Then we evaluated the proportion of stands’ area which survives up to a certain age. To analyze the data, we applied MS Excel and MapInfo Mapping Package. Results and Conclusions The probability of silver birch survival in the Left-Bank Forest-Steppe was evaluated depending on the region, the type of forest site conditions, the origin, the site index of the stands and the proportion of silver birch in the composition. We came to the conclusion that survival of silver birch in almost all age classes is the lowest in the relatively poor forest site conditions and is the highest in the most of age classes in fresh fertile forest site conditions. Moreover, the mean weighted age class of silver birch in the Left-Bank Forest-Steppe is IV.8 in vegetative stands and IV.6 in artificial seed stands. For all origins, the mean weighted age class is V.1 for Sumy Region and IV.6 for Kharkiv and Poltava Regions. The stands of the worse growth have the least longevity. A survival rates of pure (100 % silver birch) and almost pure (90 % silver birch) stands are the lowest. The stands with 50–70 % of silver birch have the highest survival level. The stands with a low silver birch proportion (up to 40 %) take an intermediate position. Survival of pure and almost pure silver birch stands is the highest in Sumy Region. To conclude, it is necessary to provide a possibility to reduce the age of the main felling if there is a risk of decrease in timber quality in case of expectation of the deadline for the main felling in accordance with existing standards. 4 Figs., 5 Tables, 7 Refs.